RESEARCH ON KINETIC OF CARBON REDUCING PROCESS OF MOLTEN CAO-FEOX-SIO2 SYSTEM - Zhang L.; Wang M.; Sui Z. (My University, 2005)
In the study of selective precipitate copper slag treating process, carbon powder was added into slag and stir with inertia gas, viscosity of slag reduced so as to accelerate copper deposition. Relationship between content of Fe(II) in the slag and ratio of addition carbon and relationship between Cu remained, viscosity and content of Fe(II) were investigated. Microstructure of the slag was observed by metalographic microscope and SEM and phase compositions were determined by EDX and XRD. The variation of ferrous content in the slag at different reduction time was obtained by chemical analysis method, from which the kinetic equations of the carbon reduction were deduced. The results show that Fe3O4 reduction reaction order is zero, and apparent activation energy Ea is 441.244 kJ·mol-1 in constant inertia gas blowing. In impoverishment process, the amounts of magnetite declined until vanished almost and the quantity of fayalite and olivine increased gradually in the carbon reduction process.
Keywords: COPPER SLAG; FAYALITE; IMPOVERISHMENT; REDUCTION PROCESS